回復期リハビリテーション病棟における手段的日常生活活動（IADL）練習の実態調査 - 金野 達也; 會田 玉美 (作業療法, 2024)
要旨：本研究は，回復期リハビリテーション病棟におけるIADL練習の実態とその関連要因を明らかにすることを目的とした．対象者は，回復期リハビリテーション病棟協会会員病棟の作業療法部門責任者900名とし，251件の回答があった．IADL練習の実施程度は対象者におけるIADL練習の価値，必要な予算，必要な時間，周囲のスタッフの理解と有意な相関がみられた．約半数は客観的評価による効果判定をしておらず，実施群のほうが，IADLニーズがあり，物理的環境があると感じていた．本研究によりIADL練習をしやすくするための示唆を得られた一方で，IADL評価を実施する必要性と簡便な評価法の開発という課題が示唆された． 　The purpose of this study was to elucidate the current conditions and factors influencing the practice of IADL in a recovery rehabilitation unit. The subjects were 900 occupational therapy department managers from member wards of the Kaifukuki Rehabilitation Ward Association, and a total of 251 responses were received. The study observed significant correlations between the degree of IADL practice implementation and factors such as perceived value of IADL practice, required budget, required time, and understanding of surrounding staff. Remarkably, around half of the participants did not conduct objective evaluations. Among the group that did conduct evaluations, there was a significantly greater perceived need for IADL practice and a better physical environment. Thus, while the study provided suggestions for facilitating the practice of IADL, it also highlighted the need to implement IADL evaluation and develop a simple evaluation method.